1999
DOI: 10.1038/sj.bjc.6690238
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL-40 and colorectal cancer

Abstract: Summary YKL-40 is a mammalian member of the chitinase protein family. Although the function of YKL-40 is unknown, the pattern of its expression suggests a function in remodelling or degradation of extracellular matrix. High serum YKL-40 has been found in patients with recurrent breast cancer and has been related to short survival. In the present study we analysed YKL-40 in preoperative sera from patients with colorectal cancer and evaluated its relation to survival. Serum YKL-40 was determined by RIA in 603 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
180
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(194 citation statements)
references
References 28 publications
13
180
0
1
Order By: Relevance
“…1 Both tumor cells and tumor-associated macrophages produce YKL-40. 2 Plasma YKL-40 is high in patients with gastrointestinal, [3][4][5] breast, 6 lung, 7 prostate 8 and other cancer, [9][10][11] and is also associated with tumour burden and prognosis after a cancer diagnosis. 5,[12][13][14][15][16] Furthermore, high plasma YKL-40 predicts high risk of gastrointestinal cancer in the general population.…”
mentioning
confidence: 99%
“…1 Both tumor cells and tumor-associated macrophages produce YKL-40. 2 Plasma YKL-40 is high in patients with gastrointestinal, [3][4][5] breast, 6 lung, 7 prostate 8 and other cancer, [9][10][11] and is also associated with tumour burden and prognosis after a cancer diagnosis. 5,[12][13][14][15][16] Furthermore, high plasma YKL-40 predicts high risk of gastrointestinal cancer in the general population.…”
mentioning
confidence: 99%
“…It was first isolated from porcine VSMC, which is highly induced during nodule formation, but the precise function of this gene is presently unknown. High serum expression of YKL-40 has been associated with poor prognosis in colorectal cancer (Cintin et al, 1999), glioblastoma multiforme (Tanwar et al, 2002), breast cancer (Johansen et al, 1995), ovarian cancer (Dehn et al, 2003), and lung cancer (Johansen et al, 2004). Consistent with the function of CLU, overexpression of YKL-40 has been implicated in increased migration and tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…22 We expected that elevated serum YKL-40 levels would return to levels within the normal range after curative resection of colorectal carcinoma, since the protein might reflect the tumor burden. The current results showed that serum YKL-40 decreased in the first postoperative blood sample six months after the operation compared to the preoperative level in 62% of the patients who had elevated preoperative serum YKL-40.…”
Section: Discussionmentioning
confidence: 99%
“…22 Like CEA, YKL-40 cannot be used as a single screening test for colorectal carcinoma, since only 26% of patients with colorectal carcinoma have elevated serum YKL-40 levels at the time of operation. 22 It has been suggested that high serum YKL-40 levels might be useful as an independent preoperative predictor for poor survival in patients with colorectal carcinoma. 22 However, a prognostic marker specifically associated with the presence of a tumor may be changed by resection of the tumor.…”
mentioning
confidence: 99%
See 1 more Smart Citation